The Phenology of Synαnthedon myopαeformis Borkhausen (Lepidoptera: Sesiidae) in the Region of Larissa, Central Greece - Sahinoglou, Α.Ι.; Koutroubas, A.G.; Peka, Α.Α.; Giatropoulos, K.A. (ENTOMOLOGIA HELLENICA, 1998)
The phenology of Synanthedon myopaeformis Borkhausen. (Lepidoptera: Sesiidae) was studied in the region of Larissa, Central Greece, for three consecutive years (1993-1995). S. myopaeformis most propably completes one generation per year on apple trees. It overwinters as lavra of different sizes in the feeding tunnels in the trunk and branches. Pupation takes place from the end of March to the beginning of September with a peak in late May – beginning June. The emergence of adults takes place from late April to the beginning of October with the main peak in mid June. The larvae of the new generation start to appear from the beginning of May with a maximum in late June–beginning of July. Most of the infestation is observed in the grafting points and the pruning wounds. The results indicate that the pest becomes increasingly important in the study area. This study could be useful in determining the optimum timing of control measures.